(untitled) (Bangladesh Journal of Plant Taxonomy, 2009)
Anatomical properties of two morphologically distinct forms (Form I: with violet coma and Form II: without coma or with white, green or pink coma) of Salvia viridis L. have been studied. The analysis provided here studying the cross-sections of root, stem, leaf, petiole, bract, calyx and corolla comprises the first detailed description for the species. The results are furnished with photographs and drawings. Although no anatomical differences were observed between the forms, S. viridis showed some differences from other Salvia species.